D’un citoyen à l’autre : les premières constitutions de Haïti et de Cuba - Sylvie Bouffartigue (Les Cahiers ALHIM)
The revolution in Haiti and Cuba, the main islands in the Caribbean world, inaugurated and closed the cycle of the Latin American independences. The history of these two slave islands which owed the wealthiness of their creoles to the production and the business of sugar, is echoing in many titles. The question of the access to the citizenship settled in a problematic way at the time of the drafting of their first respective constitution, even in contexts very different which will fall to us to specify. Indeed when breaking with the slave colonial model, it was necessary to settle, either a creole nation had to position on ethnic criteria or not. We shall base ourselves on the first constitutional texts, to determine how and according to which political and social genesis, the foundations of the collective national identity were set up in Haiti and Cuba at the beginning and at the end of the 19° century. A continent of constitutional republics, in the hands of the creoles, was emerging from the ruins of the european empires.